2020
DOI: 10.5334/irsp.363
|View full text |Cite
|
Sign up to set email alerts
|

“Free” Not to Engage: Neoliberal Ideology and Collective Action. The Case of the Yellow Vest Movement

Abstract: The purpose of this paper is to test the main hypothesis that the endorsement of neoliberal ideology, comprising beliefs and values such as personal responsibility and hedonism, is negatively associated with the engagement in the Yellow Vest (YV) movement. In a first study (N = 489), analysis of qualitative data shows that most of the YV movement grievances are system challenging. Furthermore, consistent with our hypotheses, the more participants endorsed neoliberal ideology, the less they perceived inequaliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 55 publications
(121 reference statements)
0
10
0
Order By: Relevance
“…Increases in both TSD and the precarity of lower SES life share roots in the global advancement of flexible capitalism. However, with some notable exceptions (Bay‐Cheng et al, 2015; Becker et al, 2021; Girerd et al, 2020; Sheehy‐Skeffington, 2020), few empirical studies in psychology situate findings within the structural‐cultural context of neoliberal and flexible capitalism, which has increased the temporal–spatial precarity of workers as potential “labour time” has been expanded to all hours of the day and all places (Alliez & Lazzarato, 2018; Standing, 2011). Psychological investigations of spatial (Lewicka, 2011) and temporal (Zimbardo & Boyd, 2015) orientations have often not acknowledged the historical roots of such orientations, perhaps inadvertently reifying the abstracted ways of being in time and space that typify the Global North.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in both TSD and the precarity of lower SES life share roots in the global advancement of flexible capitalism. However, with some notable exceptions (Bay‐Cheng et al, 2015; Becker et al, 2021; Girerd et al, 2020; Sheehy‐Skeffington, 2020), few empirical studies in psychology situate findings within the structural‐cultural context of neoliberal and flexible capitalism, which has increased the temporal–spatial precarity of workers as potential “labour time” has been expanded to all hours of the day and all places (Alliez & Lazzarato, 2018; Standing, 2011). Psychological investigations of spatial (Lewicka, 2011) and temporal (Zimbardo & Boyd, 2015) orientations have often not acknowledged the historical roots of such orientations, perhaps inadvertently reifying the abstracted ways of being in time and space that typify the Global North.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the present research can help nourish several research fields in psychology. For instance, it has been shown that an important implication of neoliberal ideology is that it diminishes the chances of one engaging in collective action (e.g., Girerd and Bonnot, 2020 ; Girerd et al, 2020 ). In our interviews, we did find elements that help us understand this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Neoliberalism fosters this mode of governance by promoting certain beliefs and values, by shaping people's aspirations, by psychologizing structural issues and by prescribing certain behavioral, psychological and emotional reactions (e.g., Larner, 2000 ; Beauvois, 2005 ; Pedwell, 2012 ), inasmuch as an ideology dictates how one should think, feel and react toward specific events (Ratner, 2019 ). For instance, research conducted in France has already brought some evidence that neoliberal ideology could hinder engagement in collective action aimed at addressing structural disadvantages (Girerd and Bonnot, 2020 ; Girerd et al, 2020 ). Yet, at this point more research is still needed to better grasp the content of this ideology, and thus its consequences.…”
Section: Introductionmentioning
confidence: 99%
“…A second study pointed at the potential role of antineoliberal ideology to explain participation in the YVs movement (Girerd et al, 2020), a relation mediated by a lower sense of personal control and the feeling that the system is unjust and illegitimate. This explanation deals with the notion of anomie, a general sociological concept proposed by Durkheim (1897Durkheim ( /1967 in his study about social determinants of suicide.…”
Section: Introductionmentioning
confidence: 99%